2006
DOI: 10.1007/s10653-005-9039-4
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic contamination in the Kanker district of central-east India: geology and health effects

Abstract: This paper identifies newer areas of arsenic contamination in the District Kanker, which adjoins the District Rajnandgaon where high contamination has been reported earlier. A correlation with the mobile phase episodes of arsenic contamination has been identified, which further hinges on the complex geology of the area. Arsenic concentrations in both surface and groundwater, aquatic organisms (snail and water weeds) soil and vegetation of Kanker district and its adjoining area have been reported here. The regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…The results obtained by current study for TAs, As III and As V were comparatively lower than those reported in the literature for groundwater. 28,[39][40][41] However, the mean concentration of inorganic As species were higher than the WHO recommended level for total As. 3 Thus, it was suggested that the high level of As species might be due to anthropogenic and geological activities, which may play a key role in the distribution of studied inorganic As species in water bodies.…”
Section: ×100mentioning
confidence: 85%
“…The results obtained by current study for TAs, As III and As V were comparatively lower than those reported in the literature for groundwater. 28,[39][40][41] However, the mean concentration of inorganic As species were higher than the WHO recommended level for total As. 3 Thus, it was suggested that the high level of As species might be due to anthropogenic and geological activities, which may play a key role in the distribution of studied inorganic As species in water bodies.…”
Section: ×100mentioning
confidence: 85%
“…Heavy metal mobility, bioavailability and toxicity depend largely on the chemical state of the metals and determine the potential for environmental pollution. Metal distribution depends on the characteristics of the soils being studied and corresponds to the place of origin, such as the amount and type of organic and inorganic matter, redox properties, pH and oxygen are among the most important chemical factors that affect the mobility of soil-bound metals [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Metal distribution depends on the characteristics of the soils being studied and corresponds to the place of origin, such as the amount and type of organic and inorganic matter. Redox properties, pH and oxygen are among the most important chemical factors that affect the mobility of soil-bound metals [Duris, 2002;Guo and Zhou, 2006;Pandey et al, 2006 andWinfield, 2001].…”
Section: International Journal Of Current Microbiology and Applied Scmentioning
confidence: 99%